Change Mechanisms Associated with Combined Relaxation/EMG Biofeedback Training for Chronic Tension Headache - Rokicki, Lori A.; Holroyd, Kenneth A.; France, Christopher R.; Lipchik, Gay L.; France, Janis L.; Kvaal, Steven A. (Applied psychophysiology and biofeedback, 1997)
Therapeutic mechanisms hypothesized to underlie improvements in tension headache activity achieved with combined relaxation and electromyographic (EMG) biofeedback therapy were examined. These therapeutic mechanisms included (1) changes in EMG activity in frontal and trapezii muscles, (2) changes in central pain modulation as indexed by the duration of the second exteroceptive silent period (ES2), and (3) changes in headache locus of control and self-efficacy. Forty-four young adults with chronic tension-type headaches were assigned either to six sessions of relaxation and EMG biofeedback training (N = 30) or to an assessment only control group (N = 14) that required three assessment sessions. Measures of self-efficacy and locus of control were collected at pre- and posttreatment, and ES2 was evaluated at the beginning and end of the first, third, and last session. EMG was monitored before, during, and following training trials. Relaxation/EMG biofeedback training effectively reduced headache activity: 51.7% of subjects who received relaxation/biofeedback therapy recorded at least a 50% reduction in headache activity following treatment, while controls failed to improve on any measure. Improvements in headache activity in treated subjects were correlated with increases in self-efficacy induced by biofeedback training but not with changes in EMG activity or in ES2 durations. These results provide additional support for the hypothesis that cognitive changes underlie the effectiveness of relaxation and biofeedback therapies, at least in young adult tension-type headache sufferers.